Development of new screening methodologies and preparation methods with application in amorphous solid dispersions and pharmaceutical cocrystals - Duarte, Íris Daniela Correia da Silva, 1987- (2016)
Tese de doutoramento, Farmácia (Tecnologia Farmacêutica), Universidade de Lisboa, Faculdade de Farmácia, 2016